1987
DOI: 10.1146/annurev.so.13.080187.001321
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood and Psychological Well-Being

Abstract: Recent studies suggest that parenthood may have negative consequences for the psychological well-being of adults. Adults with children at home report that they are less happy and less satisfied with their lives than other groups. They also appear to worry more and to experience higher levels of anxiety and depression. The overall difference between parents and nonparents appears to be small, although it has increased during the past two decades. Differences between parents and nonparents stem from economic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
3
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(117 citation statements)
references
References 49 publications
0
113
3
1
Order By: Relevance
“…For example, parents with children of any age living in the home (a group that includes both toddlers and teenagers) reported higher levels of distress than adults without children in the home (Bird, 1997); however, in this study, the latter group could include empty-nest or noncustodial parents, limiting interpretations of these effects. Consistent with these findings, research shows that parents' well-being remains relatively low until the child leaves the home (see McLanahan & Adams, 1987, for a review).…”
Section: Parenthood and Well-beingmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, parents with children of any age living in the home (a group that includes both toddlers and teenagers) reported higher levels of distress than adults without children in the home (Bird, 1997); however, in this study, the latter group could include empty-nest or noncustodial parents, limiting interpretations of these effects. Consistent with these findings, research shows that parents' well-being remains relatively low until the child leaves the home (see McLanahan & Adams, 1987, for a review).…”
Section: Parenthood and Well-beingmentioning
confidence: 69%
“…The evolutionary and developmental importance of parenting (Gerson, Berman, & Morris, 1991;, as well as its associated costs and rewards (Nomaguchi & Milkie, 2003), has led many social scientists to ask whether parents are better or worse off than their childless peers. Research on this topic has captured both the highs and lows of having children, with some studies indicating that parenthood is associated with higher well-being (Aassve, Goisis, & Sironi, 2012;Ballas & Dorling, 2007;Herbst & Ifcher, 2013;Myrskyla & Margolis, 2012;Nelson, Kushlev, English, Dunn, & Lyubomirsky, 2013), and others suggesting the reverse (Evenson & Simon, 2005;Glenn & Weaver, 1979;McLanahan & Adams, 1987). Accordingly, the association between parenthood and wellbeing has become a hot topic among sociologists, psychologists, and economists, as well as the media and the general public.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the association between parenthood and depression remains inconclusive. Some studies showed that children decrease the mental wellbeing of parents or do not have a significant influence (Glenn and McLanahan 1981;McLanahan and Adams 1987;Ross, Mirowsky and Huber 1983), whereas other studies found a positive association with the parents' mental wellbeing (Kandel, Davies and Raveis 1985;Burton 1998;Helbig et al 2006). Recent evidence suggests that childlessness is associated with enhanced wellbeing, at least for certain social groups in society (Umberson, Pudrovska and Reczek 2010).…”
Section: Ties With Childrenmentioning
confidence: 99%
“…It also reduces happiness (Glenn & McLanahan, 1982;Glenn & Weaver, 1978;McLanahan & Adams, 1987;Nicolson, 1999;White, Booth, & Edwards, 1986). …”
Section: Demands On Metabolic Energymentioning
confidence: 99%